Important Leadership Skills and Benefits of Shared Leadership Training for Chief Residents: A Delphi Analysis - Levy KL; Sheffield V; Sturza J; Heidemann LA (Journal of Healthcare Leadership, 2023)
Kathryn L Levy,1,2 Virginia Sheffield,1 Julie Sturza,2 Lauren A Heidemann1 1Department of Internal Medicine, University of Michigan, Ann Arbor, MI, USA; 2Department of Pediatrics, University of Michigan, Ann Arbor, MI, USACorrespondence: Kathryn L Levy, Internal Medicine and Pediatrics Department, University of Michigan, 1500 East Medical Center Drive, Ann Arbor, MI, 48109, USA, Tel +1 585 732 0597, Email kalevy@med.umich.eduBackground: Chief residents (CRs) have pivotal educational and leadership roles in residency programs. The necessary CR leadership skills that transcend specialties have not been defined and most training on these skills occurs in silo.Objective: The primary goal was to define leadership skills important for the general CR role. The secondary aim was to determine which skills should be included in cross-specialty CR training and identify benefits of such training.Methods: Sixty-three CRs and 25 program directors (PDs) from 25 residency programs at a single institution were surveyed via a modified Delphi approach in 2022 as part of a needs assessment on CR leadership training. First, respondents answered three open-ended questions about skills needed for the CR role and the potential benefits of cross-specialty CR training. Respondents then rated categorized responses on the importance of the skill, agreement that skills should be included in cross-specialty training, and agreement on benefit of cross-specialty training using a 5-point Likert scale. Positive consensus was defined as 80% agreement.Results: Fifty respondents (53%) participated in round one and 28 (32%) in round two. Positive consensus was reached on 38 skills (63%). Nine skills reached consensus on inclusion in cross-specialty training including communication skills and certain management skills. Consensus on benefits of training include learning from and collaborating with other residency programs.Conclusion: The authors defined important skills for the CR role that reached consensus across a broad range of specialties and identified the perceived benefits of shared leadership training. Residency programs should consider cross-specialty leadership training for CRs with a focus on communication and management skills.Keywords: chief residents, leadership skills, leadership training, cross-specialty training